(untitled) (Journal of actual problems of jurisprudence, 2021)
The article is devoted to current issues of legal regulation of electronic document management in the world practice and at the national level. The aim of the article is to provide the reader with some informations at studying the features of international legal and national regulation of relations taking shape in the field of electronic document management. The main goal of the article is a comparative analysis of the norms of international legal regulation of electronic document management in various legal systems. The authors came to the conclusion that Estonia’s experience in the legal regulation of electronic document management should be introduced into the Kazakhstan electronic document management system, since Estonia was the first in the world to elect parliament through the Internet, the first to con- duct an electronic population census. Estonia has one of the most developed electronic identification systems in the world using ID cards, which provides citizens with access to any electronic service in the country. During the research of the questions posed that has been made, there were used several methods, including: logical, formal, analytical. In addition, private scientific methods were used in the work: structural-system analysis, concrete historical, comparative legal, logical, statistical methods, etc.